Criteria for Auditing the Efficiency of Natural Resource Use. Example of the Karaganda Region - ZHUPYSHEVA, Aktoty Oiratovna; MAKYSH, Serik Bihanuly; BEISENOVA, Raikhan Rymbaevna; BEISENOVA, Lyazzat Ziyadenovna; TAZITDINOVA, Rumiya Maratovna (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019, 2020)
The limited reserves of many natural resources, as well as their irrational use, poses an urgent problem of increasing the efficiency of their use by conducting a proper environmental audit. The article discusses the criteria for the audit of the effectiveness of the use of natural resources in international practice, as well as the adaptation of these criteria to the practice of conducting a state environmental audit in the Republic of Kazakhstan (on the example of industry in the Karaganda region). The article also considers the environmental and economic criteria for the efficiency of natural resource use, as well as the interrelation of these criteria by the method of correlation of indicators.